2004
DOI: 10.1097/01.coc.0000138965.97476.0f
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Reliability and Validity Testing of a New Skin Toxicity Assessment Tool (STAT) in Breast Cancer Patients Undergoing Radiotherapy

Abstract: Clear consensus on the clinical evaluation of acute skin toxicity among cancer patients undergoing radical radiotherapy (RT) is currently lacking. This study investigates the reliability and validity of a new Skin Toxicity Assessment Tool (STAT) to evaluate the objective and subjective manifestations of RT-induced acute skin effects. The STAT was designed by a multidisciplinary team involved in the management of radiation skin reactions. The tool has 3 components: patient and treatment parameters, observer sco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
40
0
5

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(46 citation statements)
references
References 24 publications
1
40
0
5
Order By: Relevance
“…However, there are few scales that determine the effect of skin reactions on patient comfort levels [13,14]. The RISRAS, developed by Noble-Adams [14] and later modified by MacBride et al [5], includes a participant component, which scores symptoms such as pain, itchiness and burning, in addition to the researcher component, which scores the visual extent of the skin reaction.…”
Section: Skin Assessmentsmentioning
confidence: 99%
“…However, there are few scales that determine the effect of skin reactions on patient comfort levels [13,14]. The RISRAS, developed by Noble-Adams [14] and later modified by MacBride et al [5], includes a participant component, which scores symptoms such as pain, itchiness and burning, in addition to the researcher component, which scores the visual extent of the skin reaction.…”
Section: Skin Assessmentsmentioning
confidence: 99%
“…However, due to time constraints in this study, this was not done. Berthelet et al [5] also reported poor compliance in reporting the dimensions for involved skin reactions due to time requirement. The third component documented patientreported symptoms including pain from 0 to 10 on a Visual Analogue Scale, and presence of burning, pulling, or tenderness.…”
Section: Study Assessmentmentioning
confidence: 99%
“…A radiotherapy nurse then assessed the subject using UWNPS and STAT [5]. Informed consent was then obtained if the subject was eligible.…”
Section: Study Assessmentmentioning
confidence: 99%
“…Radiationinduced skin toxicity is a side effect most breast cancer radiotherapy patients (74%-100%) will experience during their treatment. [5][6][7][8] The dose to the skin can vary considerably inside and outside the treatment field. Knowledge of this dose is important in order to identify areas where unwanted skin reactions may occur.…”
Section: Introductionmentioning
confidence: 99%